Let's (Not) Talk About Pain: Mothers' and Fathers' Beliefs Regarding Reminiscing About Past Pain - Pavlova, Maria; Kennedy, Madison; Lund, Tatiana; Jordan, Abbie; Noel, Melanie (Frontiers in Pain Research, 2022)
Children's memories for past pain set the stage for their future pain experiences. Parent-child reminiscing about pain plays a key role in shaping children's pain memories. Parental beliefs about the functions of reminiscing are associated with parental reminiscing behaviors. To date, no studies have investigated parental beliefs regarding the functions of reminiscing about past pain or the associations between parental beliefs and reminiscing about past pain. This study aimed to fill these gaps. One-hundred and seven parents (52% fathers) of young children were asked about their beliefs regarding reminiscing about past pain. Interview data were first analyzed using inductive reflexive thematic analysis. A coding scheme was created based on the generated themes to quantitatively characterize parental beliefs. Parents also reminisced with their children about unique past events involving pain. Parent-child reminiscing narratives were coded to capture parent reminiscing behaviors. Inductive reflexive thematic analysis generated three major themes representing parental beliefs regarding reminiscing about past pain: “reminiscing to process past pain,” “reminiscing as a learning tool,” and “avoiding reminiscing about past pain.” Parents who endorsed avoiding reminiscing used fewer optimal reminiscing elements (i.e., open-ended questions) when reminiscing about past painful experiences with children. Parents who endorsed reminiscing to process past pain used more emotion-laden language when reminiscing about past pain. Mothers and fathers of boys and girls endorsed the reminiscing functions to a similar degree. Parents of older, vs. younger, children endorsed reminiscing to process past pain to a greater degree. Developmental considerations and clinical implications of the findings are discussed.